Bioslurping - Horizontal Radial Flow - Theory and Experimental Validation - S. S. Di Julio; W. H. Shallenberger (Journal of Hazardous Substance Research, 2001)
Two-dimensional (2-D) analytical equations to describe horizontal radial flow (HRF) have been developed. An HRF test cell has been designed and fabricated. Measurements of flow rate and pressure vs. radius were compared with theoretical values derived. Reasonable agreement between measurements and theory validated the analytical equations derived. These equations can form a basis for the field study of the remediation process known as “bioslurping,” used for removal of light nonaqueous-phase liquid (LNAPL).
Keywords: bioslurping; free product recovery; multiphase recovery; bioventing; horizontal radial flow